Digital organization of Plastic Surgery Service - Aluísio Gonçalves Medeiros; Marco Tulio Rodrigues da Cunha; Luciana Rodrigues da Cunha Colombo Tiveron; Manoel Pereira da Silva; Marco Aurélio de Oliveira Marinho; Carlos Renato Rodrigues da Cunha; Vaneila Adrieli Padilha; João Pedro Rodrigues Pereira (Revista Brasileira de Cirurgia Plástica, 2019)
The attention and enthusiasm of doctors in the pre- and postoperative period is of extreme importance in maintaining good doctor/patient relationships. An adequate organization and documentary record contributes to achieving a good relationship and ensures an important legal tool for physicians. With current technological advances, the electronic medical record is a secure and democratic way to deal with this information. The government has sought to implement this system in public institutions; however, results are still modest, perhaps mainly due to the lack of resources for investment in this area. In light of this, and given the relevance of practical, informative, and dynamic medical records, we aim to present our experience with the use of a complementary digital resource that is commonly associated with medical records and uses a free of cost digital platform for storing data in the "cloud". This system can provide additional information about each patient, including outpatient follow-up, as well as photographic records of the pre-, intra-, and post-operative periods, and also facilitates quick, synchronized, and remote access through the internet. The system generates optimization of resources, surgical planning, and improvement in patient/ doctor relationships. It also leads to greater integration of the medical team, particularly in the discussion of cases and distribution of surgeries by preceptors and residents. Thus, it is an alternative resource to improve medical charts with important data regarding the performance of medical teams, paying special attention to the peculiarities of plastic surgery.